Counselling for Sustaining Quality of Life in Old Age: Introducing the German Research Project BELiA - Stefan Pohlmann; Paula Heinecker; Christian Leopold (Social Work and Society, 2012)
In Germany, social advisory services provision is abundant but confusing. Complex service structure, insufficient transparency, and overlapping services cause access barriers, especially for older clients. A current research project aims to develop a new taxonomic system for existing advisory and counselling services to help older clients orientate in the service landscape. The specific needs of older clients also call for specific qualification of advisory and counselling professionals. The project focuses on standardized qualification for advisers, approaching the subject from a social gerontology point of view. A new training plan will provide basic gerontological competences and lead to a better understanding of the quality of life in old age. The empirical design consists of a quantitative online survey among service professionals (interim N=551), qualitative interviews of experts, service providers and users (N=162), focus groups (N=96), and observation of counselling sessions (N=30). The research project is funded by the German Federal Ministry of Education and Research.